2018
DOI: 10.1055/s-0038-1669492
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Chronic Subdural Hematoma: Clinical and Imaging Risk Factors

Abstract: Background Chronic subdural hematoma (CSDH) is a major cause of neurosurgical emergencies in the elderly. Despite the use of routine surgical practices, recurrence of this condition is expected. This study was conducted to identify the risk factors (RF) for recurrent CSDH. Methods Between January 2016 and July 2017, 103 consecutive patients suffering from CSDH were admitted to our department. The no-recurrence group (NRG) consisted of 91 patients, and the recurrence group (RG) consisted of 12 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Recurrence of chronic subdural hematoma is associated with higher mortality and morbidity. 6,[9][10][11][12][13] So, choosing appropriate surgical technique is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence of chronic subdural hematoma is associated with higher mortality and morbidity. 6,[9][10][11][12][13] So, choosing appropriate surgical technique is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
“…Rouzbeh et al reported that the strongest predictors of reoperation of cSDH were clopidogrel or warfarin use, hematoma loculation on preoperative CT, and the amount of hematoma evacuation on the first postoperative CT. 12 In another study, Benaissa et al detected antiplatelet usage and right side as risk factors among various comorbidities studied for recurrent cSDH. 13 Another factor to be considered after the surgical procedure is placement of subdural drain.…”
Section: Discussionmentioning
confidence: 99%